Regulation and action of fibroblast growth factor 17 in bovine follicles - Machado, M. F. [UNESP]; Portela, V. M.; Price, C. A.; Costa, I. B. [UNESP]; Ripamonte, P. [UNESP]; Amorim, Renée Laufer [UNESP]; Buratini, J. [UNESP] (Bio Scientifica Ltd, 2009)
Fibroblast growth factor 17 (FGF17) is a member of the FGF8 subfamily that appears to be relevant to folliculogenesis and oogenesis, as the prototype member FGF8 is an oocyte-derived protein that signals to cumulus cells. FGF8 has structural and receptor-binding similarities to FGF17, whose expression in the ovary has not been reported. In this study, we demonstrate localization of FGF17 protein to the oocyte of preantral follicles, and to the oocyte and granulosa cells of antral follicles. Real-time PCR demonstrated the presence of mRNA in oocytes and, to a lesser extent, in granulosa and theca cells. FGF17 mRNA abundance was low in granulosa and theca cells from healthy follicles and increased significantly in atretic follicles. Addition of FSH or IGF-1 to granulosa cells in vitro decreased FGF17 mRNA abundance, and treatment with FGF17 inhibited estradiol and progesterone secretion from granulosa cells in relation to control Cultures without these additives. We conclude that FGF17 is a potential mediator of granulosa cell differentiation. Journal of Endocrinology (2009) 202, 347-353